2017
DOI: 10.4236/ojn.2017.711097
|View full text |Cite
|
Sign up to set email alerts
|

The Lived Experience of Parents of Children with Sickle Cell Disease: A Qualitative Study

Abstract: Background: Sickle cell disease is an inherited hematological disorder that inflects complex demands on the lives of the children and their families. Aim: To describe the lived experience and everyday strains of parents of sickle cell disease children. Methods: A descriptive qualitative approach was used. Data were collected using face-to-face interviews with 11 parents of children with sickle cell disease in Jordan. Results: Emerged themes were: 1) the catastrophe, which summarized the effect of the confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Preventive programs such as genetic screening for SCD or carrier state before marriage or pregnancy is one of the most effective means of reducing the burden of SCD [ 26 ]. Unfortunately, Ali and Razeq noted that caregivers of children with SCD in their study did not know their carrier status, until the first diagnosis of their children [ 27 ]. One reason for the inadequate knowledge on the cause of SCD could be the inadequacy of genetic counseling, which is intended to provide empirical information about genetics to help individuals understand the impact of a genetic diagnosis on their life and that of their children.…”
Section: Discussionmentioning
confidence: 99%
“…Preventive programs such as genetic screening for SCD or carrier state before marriage or pregnancy is one of the most effective means of reducing the burden of SCD [ 26 ]. Unfortunately, Ali and Razeq noted that caregivers of children with SCD in their study did not know their carrier status, until the first diagnosis of their children [ 27 ]. One reason for the inadequate knowledge on the cause of SCD could be the inadequacy of genetic counseling, which is intended to provide empirical information about genetics to help individuals understand the impact of a genetic diagnosis on their life and that of their children.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this causes inconveniences for the family or caretakers of the patient, particularly since most of the patients hail from poor families and come from distant villages and towns. A recent study from Jordan has shown that caregivers, mainly parents, of SCD pediatric patients indeed suffer from many psychological and physical hardships [36]. Parents of these children, particularly the mothers, endure enormous strains and difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Although the surgery is done in Ghana, it is often a challenge due to perceived toxicity, lack of suitable donors and the cost involved. 6 7 …”
Section: Introductionmentioning
confidence: 99%